Digital human designers. (28th January 2015) - Smith, Gregory C.; Smith, Shana S.
This study creates digital human designers. Digital human designers are models of designers. Therefore, digital human designers use design methods to create designs. Digital human designers also use digital human users to create designs. Digital human users are models of users. Therefore, digital human designers use digital human users to determine the effects of designs on users. The digital human designers in this study created designs that matched user choices with 91.4% accuracies. As a result, the digital human designers in this study used design methods to fully automate the design process. The digital human designers in this study also used the digital human users in this study to determine the effects of designs on user structures. As a result, the digital human designers in this study also used the digital human users in this study to fully automate the design process.